Male Sexual Dysfunction in Mice Bearing Targeted Mutant Alleles of the PEA3 ets Gene - Laing, Michael A. (American Society for Microbiology, 2000)
PEA3, a member of the Ets family of transcriptional regulatory proteins, is expressed in a unique spatial and temporal pattern during mouse embryogenesis; its overexpression is positively correlated with HER2-mediated breast tumorigenesis in both humans and mice. To determine whether PEA3 plays a part in development and oncogenesis and to uncover its normal physiological role, we generated mice lacking functional PEA3 by gene targeting in embryonic stem cells. PEA3(−/−) mice arose from heterozygous crosses with the expected Mendelian frequency, revealing that PEA3 is dispensable for embryogenesis. PEA3 mutant mice displayed no overt phenotype and lived a normal life span. However, PEA3-deficient males failed to reproduce. PEA3 is expressed in several male sexual organs, but gross and histological analyses of the organs from PEA3(−/−) mice revealed no abnormalities. Spermatogenesis and spermiogenesis also appeared normal in mice homozygous for the PEA3 mutation, and their sperm were capable of fertilizing eggs in vitro. PEA3(−/−) males engaged in normal mating behavior, but they did not set copulatory plugs and sperm could not be detected in the uteri of females that had mated with PEA3(−/−) males. Erections could be evoked by abdominal pressure in PEA3-deficient male mice, and the results of in vitro experiments revealed that the corpus cavernosum isolated from PEA3 mutant males relaxed in response to acetylcholine. Therefore, the infertility of PEA3 mutant males involves either mechanisms proximal to the cavernosal smooth muscle or an ejaculatory dysfunction. However, PEA3 mutant mice are phenotypically distinguishable from other knockout mice with such deficits and thus provide a unique model for further investigation of male sexual dysfunction.